2020
DOI: 10.1016/j.tem.2020.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Models of Impaired Hypoglycaemia-Associated Counter-Regulation

Abstract: Impaired awareness of hypoglycaemia (IAH) affects around a quarter of patients with diabetes who receive insulin treatment. This condition is characterised by a progressive reduction in symptomatic and behavioural responses to hypoglycaemia, increasing risk of deeper drops in blood glucose, unconsciousness, and collapse. Thus, patients with IAH experience severe hypoglycaemic episodes more frequently, resulting in significant morbidity and mortality. IAH is thought to develop as a consequence of whole-body ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 99 publications
(247 reference statements)
0
10
0
1
Order By: Relevance
“…37 Secondly, both hyperinsulinemia and the hypoglycemic episodes that precede it diminish the effectiveness of counter-regulatory mechanisms during the subsequent hypoglycemic episodes. 14,37 However, the comparison of patients with and without RH did not reveal the predominance of the former group in terms of insulin concentration. Moreover, insulin levels at hours 4 and 5 of the prolonged OGTT were significantly higher in the non-RH group than in the RH group (Table 3).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…37 Secondly, both hyperinsulinemia and the hypoglycemic episodes that precede it diminish the effectiveness of counter-regulatory mechanisms during the subsequent hypoglycemic episodes. 14,37 However, the comparison of patients with and without RH did not reveal the predominance of the former group in terms of insulin concentration. Moreover, insulin levels at hours 4 and 5 of the prolonged OGTT were significantly higher in the non-RH group than in the RH group (Table 3).…”
Section: Discussionmentioning
confidence: 77%
“…[10][11][12] Research has shown that patients with diabetic neuropathy may have a higher cardiovascular risk due to compromised counter-regulatory mechanisms following a hypoglycemic episode. 13,14 On the other hand, even an adequate response to hypoglycemia, including an increased catecholamine release or corticosteroid production, can be detrimental to the cardiovascular system, promote atherogenesis, and induce hypokalemia. 8,13 Furthermore, elevated levels of C-reactive protein, interleukin-6, interleukin-8, tumor necrosis factor alpha, endothelins, or growth factors can be found in diabetic patients during hypoglycemic episodes.…”
Section: Introductionmentioning
confidence: 99%
“…This latter aspect of hypoglycemia "awareness" can be studied using a conditioned place preference test, which has so far been validated in rats but not in mice (57), largely because of the more rapid induction of defective counter-regulation in rats and their tractability for behavioral tests. The species differences between rats and mice in the adaptation to recurrent hypoglycemia are important considerations when designing a study and have been previously discussed in detail elsewhere (58). Seminal studies in rats revealed the presence of glucosensors in the hindbrain that can mount responses to restore blood glucose in the face of a glucoprivic challenge independent of forebrain structures or when the cerebral aqueduct is blocked (59,60).…”
Section: Ratsmentioning
confidence: 99%
“…The effectiveness of these protocols varies between mice and rats (and within strains of these species) with C57BLJ/6 mice being especially prone to dietinduced obesity (DIO) while inbred rat strains show both resistance or susceptibility to DIO (133,134). Similarly, rats more readily develop impaired awareness of hypoglycemia with fewer hypoglycemic bouts required for induction than mice (58). Nonmammalian species including zebrafish and drosophila also have transgenic strains that can model some facets of human disease, however, their distinct physiology from humans means that these models do not recapitulate human disease as faithfully as rodent models (135,136).…”
Section: Experimental Models Of Diabetesmentioning
confidence: 99%
“…Além da relevância do tema para compreensão de patologias, a regulação da glicemia está ligada, desde a década de 1960, à compreensão dos mecanismos fisiológicos do comportamento alimentar (Anand et al, 1964;Ritter et al, 1981;Ritter & Strang, 1982;Aklan et al, 2020). Nesse contexto, pesquisadores vêm mostrando o papel fundamental da resposta contrarreguladora (CRR) para proteger nosso organismo contra condições hipoglicêmicas graves (Cryer, 1993;Sankar et al, 2020).…”
Section: Glicose: Substrato Energético Essencial Ao Cérebrounclassified